ĐẬP THỦY ĐIỆN – NHÂN TỐ LÀM TRẦM TRỌNG THÊM TÁC ĐỘNG BIẾN ĐỔI KHÍ HẬU - Lê, Diên Dực (2016)
By reviewing negative impacts of hydroelectric dams in relation to the impacts of climate change to Vietnam, this paper tries to provide a better understanding of how this economic activity can increase or make more severe the impacts of climate change. With synthesized and analyzed practical evidence on the impacts of dams, linked to the effects of climate change from international and national literature, the paper shows that these dam-induced impacts manifest themselves in different social and ecological ways. They include increasing green-house gas emissions and a threat to river ecosystems, especially to the coastal wetlands, which increases the threat of rising sea levels and of natural disasters, such as storms and floods. These impacts can consequently make the effects of climate change more severe on local communities who depends on these ecosystems and are vulnerable to natural risks. Lack of good planning and inappropriateness of governance have been found to be factors increasing the negative impacts of these dams. To mitigate these impacts, the paper recommends, to decision makers and planners, that a national strategy for sustainable hydroelectricity development should be urgently developed, and that the option of canceling malfunctioning hydroelectric dam projects should be put into effect as soon as possible.